2016
DOI: 10.1039/c5sm01380a
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of phosphorus from surfactant solutions by wheat leaves: spreading kinetics, wetted area, and drying time

Abstract: The delivery and uptake of nutrients at the surface of plant leaves is an important physicochemical phenomenon that depends on leaf surface morphology and chemistry, fertilizer formulation chemistry (including adjuvant and associated surfactants), wetting dynamics, and many other physical, chemical and biological factors. In this study, the role of spreading dynamics in determining uptake of the macronutrient phosphorus from phosphoric acid fertilizer solution in combination with three different adjuvants was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
7
27
0
Order By: Relevance
“…An increase in biomass due to increased uptake of P from foliar application has previously been reported (Sherchand and Paulsen 1985;Mosali et al 2006;McBeath et al 2011). The high recovery (>60% in most cases) of the foliar pathway found in this study is consistent with findings from other studies that used foliar P at rates relevant for field applications (McBeath et al 2011;Peirce et al 2014Peirce et al , 2016. The efficiency of foliar P uptake was not affected by formulation, with only potassium phosphate having lower efficiency, owing to crystallisation of the fertiliser on the leaf surface, which was subsequently washed off the leaves.…”
Section: Growth Room Formulation Evaluationsupporting
confidence: 91%
See 3 more Smart Citations
“…An increase in biomass due to increased uptake of P from foliar application has previously been reported (Sherchand and Paulsen 1985;Mosali et al 2006;McBeath et al 2011). The high recovery (>60% in most cases) of the foliar pathway found in this study is consistent with findings from other studies that used foliar P at rates relevant for field applications (McBeath et al 2011;Peirce et al 2014Peirce et al , 2016. The efficiency of foliar P uptake was not affected by formulation, with only potassium phosphate having lower efficiency, owing to crystallisation of the fertiliser on the leaf surface, which was subsequently washed off the leaves.…”
Section: Growth Room Formulation Evaluationsupporting
confidence: 91%
“…The role of adjuvants in the translocation of foliar P once it enters the plant cells is still relatively unknown, although Stolzenberg et al (1982) showed that there was little movement of a labelled surfactant and its metabolites away from the initial application site. Although the type of adjuvant was not important for either uptake or translocation of foliar-applied P when used in combination with phosphoric acid as the P source (Peirce et al 2016;Peirce et al 2019), it is not known what interactions may occur between adjuvants and other P sources.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In agriculture, e.g. in pesticides crop spraying [4], oblique drop impact and the subsequent splashing and droplet rebound [5] is important. In industrial applications oblique impact occurs in e.g.…”
Section: Introductionmentioning
confidence: 99%